PERANCANGAN WEBSITE INTERAKTIF UNTUK DIGITALISASI QUALITY CONTROL PADA PRODUK WIRE PADA PERUSAHAAN OTOMOTIF - Az-Zahra; Uswatun Choiriyah (PT. Hasba Edukasi Mandiri, 2026)
Quality control is an essential aspect of manufacturing industries to ensure that products meet established standards and maintain customer satisfaction. However, conventional methods such as manual recording often cause problems, including reporting delays, input errors, and difficulties in data tracing. This research aims to design an interactive website as a digitalization system for Quality Control of wire products at PT. XYZ. The research method used is software engineering with a Waterfall approach, which includes requirement analysis, system design, implementation, and maintenance. The system was developed using the PHP programming language and MySQL database. The results show that the interactive website simplifies the process of recording, monitoring, and analyzing product defect data in real-time. Based on the economic analysis, the system can reduce operational costs from Rp6,658,244.45 to Rp3,641,066.67 per month, resulting in an efficiency of Rp3,017,177.78. Therefore, the implementation of the interactive Quality Control website is proven to be effective, efficient, and feasible to support data-driven quality management processes in manufacturing companies.